2012
DOI: 10.3163/1536-5050.100.2.008
|View full text |Cite
|
Sign up to set email alerts
|

Provision of pandemic disease information by health sciences librarians: a multisite comparative case series

Abstract: Qualitative analysis resulted in increased understanding of pandemic information needs and identified best practices for disseminating information during periods of high organizational stress caused by an influx of new cases of an unknown infectious disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 15 publications
(13 reference statements)
0
25
0
3
Order By: Relevance
“…Those in the library and information science field, particularly health and clinical librarians, could utilise the methods outlined in this study to better understand discussion around infectious disease outbreaks. Health librarians working with hospitals and the medical community may be tasked with collating information related to emerging pandemic diseases (Featherstone et al., ). Moreover, early research has noted the potential of social media and Web 2.0 technologies for developing knowledge and disseminating information as a library professional (Giustini & Wright, ).…”
Section: Implications For Practitionersmentioning
confidence: 99%
See 1 more Smart Citation
“…Those in the library and information science field, particularly health and clinical librarians, could utilise the methods outlined in this study to better understand discussion around infectious disease outbreaks. Health librarians working with hospitals and the medical community may be tasked with collating information related to emerging pandemic diseases (Featherstone et al., ). Moreover, early research has noted the potential of social media and Web 2.0 technologies for developing knowledge and disseminating information as a library professional (Giustini & Wright, ).…”
Section: Implications For Practitionersmentioning
confidence: 99%
“…To the best of our knowledge, this is the first evidence based research project applying a qualitative methodology (Braun & Clarke, 2006) to tweets generated during the peak of the 2009 swine flu outbreak. Previous empirical research has found that librarians play a role in meeting the information needs of administrators in health settings due to the ability to gather high quality information during the response phase on an infectious disease outbreak (Featherstone, Boldt, Torabi & Konrad, 2012). The ability to use social media data for consumer insights towards products or organisations known as 'social media listening' has gained in popularity in recent years (Quartey, Ley-Acosta, Pierce, Nguyen & Ertle, 2018).…”
Section: Rationalementioning
confidence: 99%
“…Concerns about pandemic influenza also resulted in medical librarians being recruited for an institutional planning task force (Tekeli-Yeşil, 2006), and four case studies from South Louisiana after Hurricane Katrina contributed to the development of planning recommendations for health sciences librarians' reference services during a disaster (McKnight, 2006). An H1N1 information service provision case series yielded accounts of successful projects as a result of medical librarian involvement in institutional preparedness activities and librarian inclusion in organizational disaster plans (Featherstone, Boldt, Torabi, & Konrad, 2012).…”
Section: Medical Librarians and Disaster Planningmentioning
confidence: 99%
“…They found a combination of self-initiated (librarian) and client-initiated (faculty, student, health care worker) services that ranged from promoting resources through social media and online channels, creating article digests, filling article requests, and monitoring ever-changing information to inform hospital policies. 10 Apart from being information providers, librarians have also played a role in planning and implementing measures to address pandemic scenarios. In a publication most relevant to the current situation, McGuire describes her and another librarian's experience in 2006 as members of a campus-level task force charged with contingency planning for educational offerings if a pandemic, at the time the re-emergence of the 2003 H5N1 influenza virus, were to disrupt classroom instruction.…”
Section: Literature Reviewmentioning
confidence: 99%